Quality Of Service And Control Governor’s Recommendation Utilization Of Northern Bandung Area In The Office Of Capital Investment And One-Stop Integrated Service The Province Of West Java - Irvan Niko Firmansyah; Soleh Suryadi; Eddy Jusuf Sp (Doctoral Program of Social Science Pasundan University, 2022)
Government is an organization that has full responsibility for the improvement of public service quality. Consequently, service becomes the prior task of the organization’s officials as civil and public servants. There are 197 licenses and non-licensed public services. Therefore, it is important to maintain and improve service quality continuously. Meanwhile, the existing service quality hasn’t shown significant results. It can be viewed from public complaints on the publication process of the governor’s recommendation of land use in the North Bandung Region. Yet, there was a lot of field control that its implementation was irrelevant to the recommendation. Complaints, indictments, and inappropriateness recommendations in the field need to be minimized in order to optimize service quality and control conducted by the West Java Provincial Government on the publication process of the governor’s recommendation of land use in the North Bandung Region. Accordingly, the researcher would like to conduct further study on how Service Quality and Control of Governor’s Recommendation of Land Use in North Bandung Region performed by the West Java Provincial Government, as well as to study strategies that can be applied in order to improve service quality. This research applied qualitative study using the snowball technique to objects of study, i.e. public service administrators; public service customers; public service observers, primarily those who are involved in the legalization of the governor’s recommendation of land use in the North Bandung Region. The data were obtained through interviews and deep analysis using triangulation observers. The research of the study reveals that the inconsistency of service quality is influenced by 10 dimensions, i.e. tangibles, reliability, responsiveness, courtesy, credibility, security, access, communication, and understanding of the consumer. On the other hand, environment control, risk assessment, control activities, information, and communication, yet monitoring control are determinant factors in controlling the governor’s recommendation of land use in the North Bandung Region. It is done by applying strategies that implement technology, innovation, and operation approach. From the research, it is found new dimensions, are: institutional coordination, supervision, collaboration, prosecution, and policy diversification through GSMALL Collaboration Model (Government, Society, Media, Academic, and Law Enforcement).